2012
DOI: 10.1590/s0004-28032012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal manometry findings and degree of acid exposure in short and long Barrett's esophagus

Abstract: -Context -Barrett's esophagus (BE) is characterized by intestinal metaplasia in the distal esophagus and is classified as short-segment (<3 cm -SSBE) or long-segment (>3 cm -LSSBE). It is suggested that LSSBE is associated with more severe esophageal motor abnormalities and increased acid exposure time than SSBE. Objective -To evaluate the prevalence of esophageal manometriy abnormalities and acid exposure times in patients with SSBE and LSSBE. Methods -Barrett's esophagus patients identified by upper endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…While patients with long-segment Barrett’s exhibited greater esophageal acid exposure than patients with short-segment Barrett’s, no difference was observed concerning esophageal contractile activity in a series of 46 Brazilian patients [60]. On the other hand, Loughney et al observed lesser esophageal peristaltic amplitude in patients with long-segment Barrett’s compared to controls [42]; a difference that was not observed in a comparison with short-segment Barrett’s patients.…”
Section: Esophageal Peristaltic Functionmentioning
confidence: 99%
“…While patients with long-segment Barrett’s exhibited greater esophageal acid exposure than patients with short-segment Barrett’s, no difference was observed concerning esophageal contractile activity in a series of 46 Brazilian patients [60]. On the other hand, Loughney et al observed lesser esophageal peristaltic amplitude in patients with long-segment Barrett’s compared to controls [42]; a difference that was not observed in a comparison with short-segment Barrett’s patients.…”
Section: Esophageal Peristaltic Functionmentioning
confidence: 99%